Elementary Teachers’ Difficulties in Team Teaching: An Exploration between Novice and Experienced Indonesian English Teachers - Ade Tika; Rita Seroja Ginting; Utami Dewi (Scope : Journal of English Language Teaching, 2023)
This research aims at exploring the difficulties faced by elementary school teachers in team teaching between novice and experienced teachers. This research was conducted in some private schools in Medan. Participants consisted of 16 teachers of which 8 teachers were chosen in participating the questionnaire and interview of 4 novice teachers and 4 experienced teachers. This research used qualitative methods and took a thematic approach to its data collection. A questionnaire with open-ended questions as well as semi-structured in-depth interviews served as the research instruments. The findings of this research reveal four common themes that emerged from the responses to the questionnaire regarding the difficulties that teachers experience during the process of team teaching and the factors that contribute to those difficulties. It is necessary to conduct additional research in order to determine whether the perspectives of team teachers working in various areas are unique or equivalent.